JURNALISME DATA : TRANSFORMASI DAN TANTANGAN ERA DIGITAL - Hartinah Sanusi (Fakultas Dakwah dan Komunikasi, 2018)
Journalism throughout the history of human civilization as the invention and technological development undergoes a transformation. The existing forms and varieties of journalism serve as a marker for every age. In today's digital age, the emergence of the explosive phenomenon of data and information gave rise to a new format for journalism known as data journalism. The presence of data journalism breaks down as well as raises a new framework of journalism. A form of journalism that adapts to principles in the era of free and open digital technology. This paper attempts to examine the study of journalism with the complexity of its change as an interesting study as well as challenging both conceptually and practically in Indonesia.